A Single Aspartate Coordinates Two Catalytic Steps in Hedgehog Autoprocessing - Xie, Jian (J Am Chem Soc, 2016)
Hedgehog (Hh) signaling is driven by the cholesterol-modified Hh ligand, generated by autoprocessing of Hh precursor protein. Two steps in Hh autoprocessing, N–S acyl shift and transesterification, must be coupled for efficient Hh cholesteroylation and downstream signal transduction. In the present study, we show that a conserved aspartate residue, D46 of the Hh autoprocessing domain, coordinates these two catalytic steps. Mutagenesis demonstrated that D46 suppresses non-native Hh precursor autoprocessing and is indispensable for transesterification with cholesterol. NMR measurements indicated that D46 has a pK(a) of 5.6, ~2 units above the expected pK(a) of aspartate, due to a hydrogen-bond between protonated D46 and a catalytic cysteine residue. However, the deprotonated form of D46 side chain is also essential, because a D46N mutation cannot mediate cholesteroylation. On the basis of these data, we propose that the proton shuttling of D46 side chain mechanistically couples the two steps of Hh cholesteroylation.